Hybrid suspension of polymer and nanoparticles for enhanced oil recovery - Gbadamosi, A.O. (2019)
Enhanced oil recovery (EOR) process is used to recover the oil left in the reservoirs after primary and secondary recovery methods. Polymer material plays an important role in oil recovery by decreasing the mobility ratio and through the mechanism of disproportionate permeability reduction. However, the application of polymer flooding for oil recovery is limited in high-temperature and high-salinity oil reservoirs due to degradation of its molecules, thereby hindering the polymer EOR process efficiency. Recently, the oil and gas industry is adopting the application of nanotechnology to solve the problem plaguing the application of polymers for EOR. This has been attributed to the nanoparticles unique properties and availability in large quantities. The addition of nanoparticles into polymer solution has been reported to improve the rheological and shear properties, and lower the adsorption of polymers, thereby consequently enhancing oil recovery. This paper reviews the current trend of incorporating nanoparticles into polymers to improve polymer flooding process by explaining the mechanism involved, opportunities offered and challenges encountered. Technical solutions to overcome the challenges identified are also discussed. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.